Strategic structuring of MTE business areas: methodical approach - Fedotova , Iryna; Bocharova, Nadiia; Litvinenko , Alina (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2025)
The article explores a methodological approach to the strategic structuring of business directions in a motor transport enterprise (MTE) under martial law and post-war recovery. Problem statement. The study focuses on Strategic Business Units (SBUs), which enable the evaluation of transport service efficiency and the optimization of managerial decisions. The main issue addressed is the absence of adapted methodologies capable of assessing internal business group positions in unstable transport markets. Unresolved aspects of the problem. Traditional approaches, particularly the BCG matrix, overlook enterprise-specific dynamics, the weight of product groups in sales, variations in transport revenues, and market turbulence, limiting their accuracy and applicability. Purpose of the article. The study aims to develop and justify a methodological approach to structuring MTE business directions through SBU identification, enabling effective management under high uncertainty caused by wartime and recovery conditions. Presentation of the main material. A stepwise SBU evaluation method is proposed, based on analyzing sales revenues, their change trends (K and T indicators), and internal financial and production parameters. For each group, the relative share in total sales and revenue change rate are calculated to classify business directions by strategic relevance: development, investment, support, optimization, or transformation. The methodology ensures an objective assessment of internal business group positions, facilitates balanced SBU portfolio formation, considers potential risks, and substantiates managerial decisions on investment, development, or optimization. Its practical significance lies in creating a strategic planning tool adaptable to enterprise resources, industry features, and organizational forms, ensuring effective operation under uncertainty. Conclusions. Further research will focus on digital models for automated SBU monitoring to enhance managerial responsiveness, strategic flexibility, and financial resilience, thereby ensuring the universality and reliability of the proposed methodology in diverse practical contexts.